TRAINING OF SPECIAL PHYSICAL QUALITIES OF STUDENTS 5-7 CLASSES IN THE SCHOOL CIRCLES OF ARTISTIC GYMNASTICS - Zokirov Ulugbek Murodjon ogli; Toshkanboyeva Zaynabbonu Obidjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
The article examines measures to properly organize artistic gymnastics clubs in general secondary schools and to increase students interest in artistic gymnastics.